2016
DOI: 10.1002/er.3491
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study on the application of diffuse-reflection concentrators in PV/T solar system

Abstract: In order to improve the practicability of PV/T solar system, we proposed the theory and method on the application of diffuse-reflection concentrator in the PV/T solar system and analyzed the concentration characteristics of this proposed application. In addition, we designed experimental prototype of PV/T solar system and conducted test and analysis of the thermal and electrical characteristics of the PV/T solar system with or without a concentrator, respectively. The results showed that for the PV/T solar sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…6 Also, water cooling can be applied to cool the front side of PV panel. Yongtai et al 5 produced a photothermal conversion model of PV/T solar water heater to optimize the PV cell coverage.…”
Section: Introductionmentioning
confidence: 99%
“…6 Also, water cooling can be applied to cool the front side of PV panel. Yongtai et al 5 produced a photothermal conversion model of PV/T solar water heater to optimize the PV cell coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Considering PV cell is tightly contacted with absorber plate, the influence of thermal contact resistance can be neglected, and thus, Q pv can be expressed as Qpv=Apv(),tpvtcδitalicpvλitalicpv+δcλc, where δ pv and δ c are the thickness of PV cell and absorber plate, respectively; λ pv and λ c are the thermal conductivity of PV cell and absorber plate, respectively; A pv is the area of PV cell; and t pv and t c are the temperature of PV cell and absorber plate, respectively. It should be noted that PV cell temperature is affected more by solar irradiance, and the correlation between plastic substrate PV cell temperature and solar irradiance can be expressed by tpv=ta+27×Ei8000.25em, where t a is environment temperature and E i is solar irradiance.…”
Section: Heat‐generated Characteristics Of Pv/t Solar Systemmentioning
confidence: 99%
“…where δ pv and δ c are the thickness of PV cell and absorber plate, respectively; λ pv and λ c are the thermal conductivity of PV cell and absorber plate, respectively; A pv is the area of PV cell; and t pv and t c are the temperature of PV cell and absorber plate, respectively. It should be noted that PV cell temperature is affected more by solar irradiance, and the correlation between plastic substrate PV cell temperature and solar irradiance can be expressed by [18]…”
Section: Heat Generated Of Pv/t Solar Collectormentioning
confidence: 99%
“…He, Xiao, and Li(2016) conducted a theoretical and experimental study on the application of diffuse‐reflection concentrators in PVT system. They showed that using such concentrators will increase the amount of the incident irradiance by 26%, and consequently, the maximum output power was increased by 11%.…”
Section: Introductionmentioning
confidence: 99%